Serum iodine concentration and its associations with thyroid function and dietary iodine in pregnant women in the southeast coast of China: a cross-sectional study - Ji, Shumi; Wu, Xiaoyan; Wu, Jiani; Chen, Diqun; Chen, Zhihui (Frontiers in Endocrinology, 2023)
Background: Iodine deficiency is a major public health problem in pregnant women. Serum iodine (SI) may represent a useful biomarker for iodine nutrition evaluation. We aimed to assess the relationship between serum iodine concentration (SIC) and urinary iodine concentration (UIC), dietary iodine, thyroid function and thyroid diseases in pregnant women in the southeast coast of China, and to provide a normal reference range of SIC for pregnant women.Methods: A multistage random sampling method was used to select the study population. We collected urine and blood samples from pregnant women and determined UIC and SIC as well as thyroid function using Arsenic-Cerium Catalytic Spectrophotometry, inductively coupled plasma mass spectrometry, and Beckman Coulter Access2 chemiluminescent immunoanalyzer and kit, respectively, and administered a questionnaire on dietary iodine intake in pregnant women.Results: There was a significant negative correlation between serum iodine and thyroid stimulating hormone (TSH) (r=-0.141) and a significant positive correlation between SI and free triiodothyronine (FT3) (r=0. 106), free thyroxine (FT4) (r=0.236), triiodothyronine (TT3) (r=0.229), total thyroxine (TT4) (r=0.433) and dietary iodine intake (r=0.068). There was a significant difference in SI levels of pregnancy between the second (78.13μg/L) and third trimester (75.37μg/L) (P=0.018). SI levels between inadequate intake (74.58μg/L) and appropriate intake (77.92μg/L) groups was statistically different (P=0.036). Low SIC was a risk factor for the development of hypothyroxinemia (adjusted OR=3.14, 95% confidence interval: 1.75-5.66). The reference range for SIC in normal pregnant women is 45.03-112.44 μg/L.Serum iodine may be a composite indicator of iodine nutritional status and thyroid function.This is a provisional file, not the final typeset article Nearly 2 billion people worldwide still suffer from inadequate iodine intake (2). China used to have a high prevalence of iodine deficiency disorders (3).